Fungsi Zeta Riemann Genap Menggunakan Bilangan Bernoulli - Maulidi, Ikhsan; Apriliani, Vina; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2019)
In this article, we study about the value of Riemann Zeta Function for even numbers using Bernoulli number. First, we give some basic theory about Bernoulli number and Riemann Zeta function. The method that used in this research was literature study. From our analysis, we have a theorem to evaluate the value of Riemann Zeta function for the even numbers with its proving.